Renewable Energy & Energy Efficiency - Canal UC Berkeley Events / YouTube
California & The Future of Environmental Law & Policy Renewable Energy & Energy Efficiency -- From California to the World Karen Douglas, Commissioner, California Energy Commission, Sacramento, CA Alex Farrell, Director, Transportation Sustainability Research Center; Professor, Energy and Resources Group, University of California-Berkeley Berkeley, CA Dian Grueneich, Commissioner, California Public Utilities Commission, San Francisco, CA Steve Weissman, Associate Director for Energy Law and Policy, CCELP, University of California-Berkeley, Berkeley, CA